A Prospective Comparison of the 21-Gene Recurrence Score and the PAM50-Based Prosigna in Estrogen Receptor-Positive Early-Stage Breast Cancer - Alvarado, Michael D. (Adv Ther, 2015)
INTRODUCTION: The 21-gene Recurrence Score(®) assay (Oncotype DX(®), Genomic Health, Inc.) is a validated predictor of recurrence risk/chemotherapy benefit in patients with estrogen receptor-positive (ER+) early-stage breast cancer treated with endocrine therapy. The Prosigna(®) assay (NanoString Technologies Inc.) is a validated prognosticator in postmenopausal patients with low-risk ER+ early-stage breast cancer treated with endocrine therapy. The assays were analytically/clinically developed and validated differently. This study focused on comparing recurrence risk estimates as determined by these assays and is the first blinded comparison of these assays on matched patient samples. METHODS: Sequential breast cancer specimens from postmenopausal, node-negative, ER+ patients treated at the Marin General Hospital were analyzed: first by the 21-gene assay then by the Prosigna assay in an independent lab blinded to the Recurrence Score results. RESULTS: The final analysis included 52 patients. Correlation between the Recurrence Score and the Prosigna assay results was poor (r = 0.08). Agreement between risk classifications based on these assays was 54%; 4/7 of patients classified as high risk by the Prosigna assay had low Recurrence Score results. Two tumors with high Recurrence Score results had low ER expression (close to positivity threshold); both of which had a low/intermediate Prosigna assay result. The Prosigna assay classified 73.1% and 23.1% of samples as luminal A and luminal B, respectively. A range of Recurrence Score results was observed within the subtypes; 83% of luminal B samples had a low Recurrence Score result. CONCLUSION: Consistent with prior comparisons between the 21-gene and other genomic assays, our study demonstrated substantial differences in the way patients are risk stratified, suggesting that the different assays are not interchangeable. FUNDING: Genomic Health, Inc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12325-015-0269-2) contains supplementary material, which is available to authorized users.